Promoting the adoption of innovations through participatory approaches: example from northern Nigeria - Abdoulaye, Tahirou; Amaza, P.S.; Olanrewaju, A.S.; Ellis-Jones, J. (2012)
Participatory research and development approaches involving all stakeholders along the value chain have recently been hypothesized to produce quicker outcomes than the linear technology transfer model. This paper analyzed the crop yield obtained by farmers and their uptake of improved technologies in a 2009 survey, one year after the completion of project field activities. It was a multi-stakeholder project involving research, extension, farmer groups, marketers and policymakers, that operated for 4 years (2005-2008) in Borno state of Nigeria. Survey results indicated that farmers who participated in project activities’ have been successful in increasing crop yields. Both yields and per capita production of major crops were statistically significantly higher (ρ≤ 0.05) in project communities compared to non-project ones. It is also estimated that there was a decline in percentage of households in food insecurity situation in project communities. Probit regression revealed that participation in project activities had a positive and significant effect on household food security (ρ≤ 0.05). It is then concluded that development interventions that involve multiple stakeholder partnership, use of participatory research and extension approach can help increase technology uptake among resourcepoor farmers as well as increase food production and food security in a region.